2018
DOI: 10.1248/bpb.b18-00037
|View full text |Cite
|
Sign up to set email alerts
|

<i>O</i>-Methylbulbocapnine and Dicentrine Suppress LPS-Induced Inflammatory Response by Blocking NF-κB and AP-1 Activation through Inhibiting MAPKs and Akt Signaling in RAW264.7 Macrophages

Abstract: The natural aporphine alkaloids including crebanine (CN), O-methylbulbocapnine (OMP), and dicentrine (DC), and protoberberine alkaloids, tetrahydropalmatine (THP) and N-methyl tetrahydropalmatine (NTHP), have been found in Stephania venosa. Previous reports demonstrated CN and THP exhibited anti-inflammatory properties. In this study, we investigated anti-inflammatory effect of CN analogs including OMP, DC, THP, and NTHP in RAW264.7 macrophages. The pre-treatment of macrophages with CN, OMP and DC suppressed l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 39 publications
(43 reference statements)
2
24
0
Order By: Relevance
“…NF-κB is the major transcription factor of the inflammatory response to LPS. LPS-induced MAPK signaling pathways have been implicated in the inflammatory response through NF-κB activation (2830). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…NF-κB is the major transcription factor of the inflammatory response to LPS. LPS-induced MAPK signaling pathways have been implicated in the inflammatory response through NF-κB activation (2830). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of NF-κB and its gene cascade may be modulated by the PI3K/Akt signaling pathway, which serves an important role in cell proliferation, apoptosis and inflammation (34). Furthermore, the expression of pro-inflammatory cytokines including IL-6 and TNF-α, are influenced by NF-κB and activator portein-1 activities (35). The present study confirmed that TIPE2 inhibits the AKT signaling pathway and NF-κB activation in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, this study conducted higher concentration of cepharanthine than that of Kondo's study to evaluate the antiinflammatory activity. Dicentrine (39) at the concentrations of 5.90, 7.52 or 10.0 lM was shown to suppress LPS-induced inflammation by blocking the activation of NF-jB and activator protein-1 (AP-1) through inhibition of mitogen-activated protein kinase (MAPK) and p-protein kinase B (Akt) signaling in RAW264.7 macrophages (Yodkeeree et al 2018). Although this study assessed the cytotoxicity to RAW264.7 macrophages, anti-inflammatory effects and the mechanism of action, these authors did not compare the efficacy of dicentrine with a positive control.…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%
“…,Wang et al (2016a, b, c),Shen et al (2001),Choi et al (2000),Kang et al (2014),Wu and Ng (2007),Xu et al (2016a, b),Wu et al (2015),Nakamura et al (1992),Yang et al (2018a, b),Kondo et al (1993),Aota et al (2018),Yodkeeree et al (2018),Haque et al (2018) Anticancer/ antiproliferative effects…”
mentioning
confidence: 99%